Engagement of an optimized lentiviral vector enhances the expression and cytotoxicity of CAR in human NK cells. (March 2023) - Guo, Changjiang; Chen, Han; Yu, Jie; Lu, Hui; Xia, Qing; Li, Xiaojuan; Guo, Xiali; Wang, Tong; Zhi, Lingtong; Niu, Zhiyuan; Zhu, Wuling
Abstract: Adoptive chimeric antigen receptor (CAR)-modified T or NK cells (CAR-T/NK) have emerged as a novel form of disease treatment. Lentiviral vectors (LVs) are commonly employed to engineer NK cells for the efficient expression of CARs. This study reported the influence of single-promoter and dual-promoter LVs on the CAR expression and cytotoxicity of engineered NK cells. We constructed a third-generation NKG2D-based CAR that kills cancer cells by targeting up to eight stress-induced ligands (NKG2DLs). Our results demonstrated that the CAR exhibits both a higher expression level and a higher coexpression concordance with the GFP reporter in HEK-293T or NK92 cells by utilizing the optimized single-promoter pCDHsp rather than the original dual-promoter pCDHdp. After puromycin selection, the pCDHsp produces robust CAR expression and enhanced in vitro cytotoxicity of engineered NK cells. Therefore, infection with a single-promoter pCDHsp lentivector is recommended to prepare CAR-engineered NK cells. This research helps to optimize the production of CAR-NK cells and enhance their functional activity, to provide CAR-NK cell products with better and more uniform quality.